Peran Komunikasi Kelompok Dalam Pembelajaran Kolaboratif Pada Pendidikan Jasmani - Hesar, Rumeli; Rahayu Rahmadini (MEDIOVA: Journal of Islamic Media Studies, 2025)
Collaborative learning in physical education emphasizes cooperation among students to achieve common goals through structured physical activity. One key factor in the success of this learning model is group communication. This article aims to examine the role of group communication in enhancing the effectiveness of collaborative learning in physical education. This research uses a literature review approach by reviewing previous research related to group communication, collaborative learning, and physical education. The results indicate that group communication plays a crucial role in building coordination, increasing student engagement, fostering mutual trust, and developing social and emotional skills. This article also discusses practical implications for physical education teachers in designing communication-based learning strategies. Thus, group communication is a crucial foundation for the success of collaborative learning in physical education.